2022
DOI: 10.1097/md.0000000000031055
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology and molecular docking reveal the mechanism of Angelica dahurica against Osteosarcoma

Abstract: Osteosarcoma (OS) is a malignant bone tumor of mesenchymal origin. Angelica dahurica is a typical traditional Chinese herb. Angelica dahurica is used in the treatment of a variety of tumors. However, the studies of Angelica dahurica for OS have not been reported. To investigate Angelica dahurica's potential mechanism of action in the treatment of OS, we used network pharmacology and molecular docking methods in this study. Of which the network pharmacology includes the collection of active ingredients of Angel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…For example, Zhao et al reported that Polygonum cuspidatum inhibits Akt/ERK/EGFR pathways to exert its effects on the cell cycle and apoptosis of OS cells 16 . Zhang et al have also shown that Angelica dahurica targets multiple pathways, including the MAPK signaling pathway, PI3K-Akt signaling pathway, and TNF signaling pathway, to treat OS by acting on multiple targets, such as ESR and TNF 17 . Curcuma is also a commonly applied TCM with anti-inflammatory, anticoagulant, analgesic, antitumor, hypolipidemic, and other pharmacological effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhao et al reported that Polygonum cuspidatum inhibits Akt/ERK/EGFR pathways to exert its effects on the cell cycle and apoptosis of OS cells 16 . Zhang et al have also shown that Angelica dahurica targets multiple pathways, including the MAPK signaling pathway, PI3K-Akt signaling pathway, and TNF signaling pathway, to treat OS by acting on multiple targets, such as ESR and TNF 17 . Curcuma is also a commonly applied TCM with anti-inflammatory, anticoagulant, analgesic, antitumor, hypolipidemic, and other pharmacological effects.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted literature searches on the treatment of insomnia using Chinese and English keywords such as “insomnia” through several databases, including China National Knowledge Infrastructure, Wanfang Data, China Science and Technology Journal Database (Zhou et al., 2022) and National Center for Biotechnology Information. In addition, we searched for relevant literature on the treatment of insomnia using traditional Chinese medicine and food through databases, such as Traditional Chinese Medicine Information Database (TCMID) (Huang et al., 2018), Traditional Chinese Medicine Integrated Database (TCM) (Fang et al., 2021), Symptom Mapping (SymMap) (Wu et al., 2019), and Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) (Zhang et al., 2022). These searches will provide a comprehensive understanding of the current state of research on treating insomnia using both conventional and traditional Chinese medicine approaches.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we utilized TCMSP (https://tcmsp-e.com/) (Zhang et al., 2022) to screen for active ingredients in medicinal and food homologous substances (Panossian et al., 2022). We employed pharmacokinetic parameters as screening conditions for active ingredients in traditional Chinese medicines, setting the oral bioavailability (OB) to ≥30% and drug‐likeness (DL) to ≥0.18.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations